Assessment of radon levels in multistory buildings on example of eight Russian cities - M. V. Zhukovsky; I. V. Yarmoshenko; A. D. Onishchenko; G. P. Malinovsky; A. V. Vasilyev; E. I. Nazarov (Радиационная гигиена, 2022)
In this work, the results of radon concentration measurements in samples of multi-storey apartment buildings in eight large cities of Russia are analyzed. Two samples, depending on the year of construction of the building – before and after 2000, were formed in each city on the basis of a quasi-random approach. Radon concentration measurements were performed using radon radiometers equipped with the CR-39 solid-state nuclear track detector. In the flats of multi-storey buildings, two radiometers were installed and flat’s average radon concentration was calculated. The exposure period for the radon radiometers was three months. To estimate the average annual radon concentration, seasonal coefficients calculated for the primary radon entry from building materials were used. In total, radon concentration measurements were carried out in 1032 flats. It was assumed that the combined sample for the cities of Ekaterinburg, Krasnodar, Nizhny Novgorod, Novosibirsk, Tyumen, and Chelyabinsk is representative for the multi-storey buildings in non-capital cities of Russia. The following arithmetic mean annual radon concentrations were obtained in samples of houses built up before and after 2000, respectively: Moscow – 17 and 21 Bq/m3; St. Petersburg – 15 and 25 Bq/ m3, the group of non-capital cities – 25 and 31 Bq/m3. Taking into account the contribution of each group of buildings to the general urban housing stock, the parameters characterizing the radon concentration in multi-storey multi-apartment urban buildings in Russia were calculated as follows: arithmetic mean 25 Bq/ m3; geometric mean 21 Bq/m3; the geometric standard deviation is 1.81. In general, exposure to indoor radon in multi-storey urban buildings in Russia is low both in terms of average value and range of concentrations. There is a tendency towards an increase in indoor radon exposure of the population in new buildings, which is associated with the introduction of construction technologies that increase the energy efficiency of buildings.